2017
DOI: 10.7287/peerj.preprints.3311v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population structure and phenotypic variation of Sclerotinia sclerotiorum from dry bean (Phaseolus vulgaris) in the United States

Abstract: The ascomycete pathogen Sclerotinia sclerotiorum is a necrotrophic pathogen on over 400 known host plants, and is the causal agent of white mold on dry bean. Currently, there are no known cultivars of dry bean with complete resistance to white mold. For more than 20 years, bean breeders have been using white mold screening nurseries with natural populations of S. sclerotiorum to screen new cultivars for resistance. It is thus important to know if the genetic diversity in populations of S. sclerotiorum within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…Several studies have 80 demonstrated genotypic differentiation of S. sclerotiorum populations from different 81 geographic regions. For example, Kamvar et al showed that populations of S. 82 sclerotiorum from Mexico shared no multilocus haplotypes with populations from the 83 United States, Australia and France (26). Similarly, Lehner et al showed that 29 % of 84 variance within a sample of isolates from southeastern Brazil and the United States was 85 explained by differences between populations from the two regions (27).…”
Section: Introduction 42mentioning
confidence: 99%
“…Several studies have 80 demonstrated genotypic differentiation of S. sclerotiorum populations from different 81 geographic regions. For example, Kamvar et al showed that populations of S. 82 sclerotiorum from Mexico shared no multilocus haplotypes with populations from the 83 United States, Australia and France (26). Similarly, Lehner et al showed that 29 % of 84 variance within a sample of isolates from southeastern Brazil and the United States was 85 explained by differences between populations from the two regions (27).…”
Section: Introduction 42mentioning
confidence: 99%
“…For instance, a recent study found a total of 15 MCG, but only seven of them were congruent, which may suggest four loci controlling mycelial compatibility segregating in the population (Attanayake et al 2012). However, considering that identical MCG from disparate regions and haplotypes have been found, this explanation does not scale well (Kohli et al 1992;Ford et al 1995;Kamvar et al 2017).…”
Section: Do Mycelial Compatibility Groups Represent Clonal Lineages?mentioning
confidence: 93%
“…The conflict between MCG and VCG documented by Ford et al (Ford et al 1995), while perplexing, may serve to explain complex relationships that continue to be observed between MCG and haplotypes (Schafer and Kohn 2006;Attanayake et al 2012;Kamvar et al 2017).…”
Section: Do Mycelial Compatibility Groups Represent Clonal Lineages?mentioning
confidence: 99%
See 2 more Smart Citations